Implementation Of Media Picture Cards And Crossword Puzzle In Learning Civics Education To Improve Study Motivation In Class VI MI Miftahul Abror - Tata Pangarsa, Abd Azis (Proceeding of International Conference on Islamic Education (ICIED); Vol 4 No 1 (2019): Proceeding of International Conference on Islamic Education (ICIED), 2019)
Responsibilities and duties of all components of MI Miftahul Abror Tawangargo Village Karangploso District Malang Regency, to be able to improve the quality of educational services to their students. So MI Miftahul Abror becomes an institution that is empowered to produce human resources who are disciplined, innovative, creative, competitive, have advantages, are characterized and have self-awareness to carry out the values ​​of Pancasila in everyday life. From the results of the assessment it can be proven that the implementation of the picture cards and crossword puzzle media in the development of motivation to learn the students of MI MI Miftahul Abror's class has been successful, so that they can develop their talents, potential and achievements. The effective form of application is carried out in accordance with procedures that have been made before. Potential students to become good social creatures, respect and respect for each other without distinguishing differences in religion, ethnicity, race, language and others in accordance with the Civics Education theme taught by teachers can be instilled since childhood. Student achievement can also increase, because of the high motivation and enthusiasm in learning by using learning media that has been developed by the teacher.